Metagenomic recovery of phage genomes of uncultured freshwater actinobacteria - Ghai, Rohit; Mehrshad, Maliheh; Mizuno, Carolina Megumi; Rodriguez-Valera, Francisco (The ISME journal, 2017)
Low-GC Actinobacteria are among the most abundant and widespread microbes in freshwaters and have largely resisted all cultivation efforts. Consequently, their phages have remained totally unknown. In this work, we have used deep metagenomic sequencing to assemble eight complete genomes of the first tailed phages that infect freshwater Actinobacteria. Their genomes encode the actinobacterial-specific transcription factor whiB, frequently found in mycobacteriophages and also in phages infecting marine pelagic Actinobacteria. Its presence suggests a common and widespread strategy of modulation of host transcriptional machinery upon infection via this transcriptional switch. We present evidence that some whiB-carrying phages infect the acI lineage of Actinobacteria. At least one of them encodes the ADP-ribosylating component of the widespread bacterial AB toxins family (for example, clostridial toxin). We posit that the presence of this toxin reflects a 'trojan horse' strategy, providing protection at the population level to the abundant host microbes against eukaryotic predators.
Keywords: High-Throughput Nucleotide Sequencing; genom virový; Actinobacteria; Fresh Water; Phylogeny; Genome, Viral; fylogeneze; Metagenomics; Bacteriophages; sladká voda; bakteriofágy; vysoce účinné nukleotidové sekvenování; metagenomika